2007
DOI: 10.1038/sj.bjp.0707174
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of apparent affinity values from H3‐receptor binding assays with apparent affinity (pKapp) and intrinsic activity (α) from functional bioassays

Abstract: Background and purpose: Agonist apparent affinities (pK I 0 ) in histamine H 3 -receptor binding assays were higher than expected from apparent affinity values (pK app ) estimated in bioassay. Here, we investigate whether the degree of pK I 0 overestimation is related to agonist intrinsic efficacy, by studying the effect of buffer composition on the pK I 0 of ligands with varying intrinsic activity. Experimental approach: In the guinea-pig ileum bioassay, intrinsic activity (a) was determined from the maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 38 publications
2
12
1
Order By: Relevance
“…In buffer A, the mean Δ H °′ values for JB96132, thioperamide and [ 3 H]clobenpropit were negative (Table 4) and mean Δ S °′ values were positive (Table 4). The mean Δ H °′ and Δ S °′ values for the ligands classified as agonists in the guinea‐pig ileum longitudinal muscle myenteric plexus (see Harper et al ., 2007 ) were also positive (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In buffer A, the mean Δ H °′ values for JB96132, thioperamide and [ 3 H]clobenpropit were negative (Table 4) and mean Δ S °′ values were positive (Table 4). The mean Δ H °′ and Δ S °′ values for the ligands classified as agonists in the guinea‐pig ileum longitudinal muscle myenteric plexus (see Harper et al ., 2007 ) were also positive (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have determined the thermodynamic parameters underlying the binding of 10 ligands (seven agonists and three antagonists) at histamine H 3 ‐receptors of guinea‐pig cortex. In previous studies, we have shown that agonist affinity values are overestimated in H 3 ‐receptor radioligand‐binding assays, when buffer does not contain salts, and that the degree of affinity overestimation is correlated with the ligand's intrinsic activity ( α ) (see Harper et al ., 2007 ). In addition, we have shown that when H 3 ‐receptor radioligand‐binding assays are conducted in the presence of salts, p K I estimates are closer to p K app values estimated by the method of Furchgott in the guinea‐pig ileum bioassay (see Harper et al ., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations